"SPLIT" Pancreaticojejunostomy in the Surgical Treatment of Chronic Pancreatitis. Issue 1 (1994) - Mulder, W.; de Jong, E.; van Gulik, T. M.; de Wit, L. Th.; van Leeuwen, D. J.; Verbeek, P. C. M.; van der Heyde, M. N.
Abstract : "Split" pancreaticojejunostomy is a procedure consisting of vertical transection of the pancreas and anastomosis of both sides of the cut pancreatic duct with an interposed, Roux-en-Y jejunal loop. In this paper we report the long term results of this procedure in the treatment of eight patients with chronic pancreatitis (CP).